Implementasi Kebijakan Etika Pegawai Negeri Sipil di Sekretriat Daerah Kabupaten Kepulauan Sula Provinsi Maluku Utara - Soamole, Mirna; Rorong, Arie; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACK The service civil  policy ethics as stipulated in Government Regulation No. 42 Year 2004 on Soul Coaching Corps and the Code of civil servants, establish ethical obligations that must be implemented by civil servants in performing official duties and relationships of everyday life. But in reality there are many civil servants attitude and behavior is not in accordance with the ethical values ​​of civil servants. Starting from these two studies in this meand to determine how the implementation of the civil service ethics policy at the District Secretariat Sula Islands. The method used was a qualitative method. Data sources / informants of this research is purposive sampling of civil servants in the Sula Islands District Secretariat is 5 persons from the leaders / officials concerned and 10 people on staff employee / executive, so the total number of informants there were 15 people. The instrument in this study is the researchers themselves, while collecting the data using interview techniques. Data  analyzed to using qualitative analysis techniques interactive model of Miles and Hubernann. The results on  based of the study conclude: 1). Actions to do by the leadership in connection with the implementation of policies such as the civil service ethics laws and regulations (PP.42 2004), fostering employee awareness, and enforcement of ethics rules is already quite effective. 2) An understanding of the ethics of civil servants are set out in PP.42 2004 (in the state of ethics, organizational ethics, ethics in society, ethics in yourself, and the ethics of others civil servants) is good enough. 3). Application of civil service ethics or practice by employees in the execution of official duties generally been pretty good, but not maximized. This means that the attitude and behavior of civil servants in performing official duties in general is quite in accordance with the ethics of civil servants specified in PP.42 2004. Based on these results the conclusion can be stated as the following suggestions: 1) The enforcement of civil servants in the Secretariat ethics to the District Sula Islands needs to be improved. 2) Understanding of the staff of the Secretariat of the islands of Sula District of ethics of civil servants need to be improved; 3) Application of civil service ethics in the execution of official duties should also be improved in environmental Sula Islands District Secretariat. In this connection it is necessary a high awareness of the employees themselves to adjust the attitude and behavior of the ethical values ​​of civil servants. Keywords: policy implementation, civil servants ethic